PENGARUH RISIKO PASAR , NILAI TUKAR , SUKU BUNGA DAN VOLUME PERDAGANGAN TERHADAP RETURN SAHAM (Studi kasus pada perusahaan yang terdaftar dalam indeks LQ45) - Buana, Gresna; Haryanto, Mulyo (Diponegoro Journal of Management, 2016)
Return is one of the factors that motivate investors to interact and also a reward for the courage of investors in risk on its investments. The purpose of this study was to analyze the effect of market risk, exchange rates, interest rates and the volume of trading on stock returns.The study population was the whole financial data LQ45 companies listed on the Stock Exchange, in the period from June 2015 to September 2015 totaling 45 companies. The sampling method used in this research is purposive sampling method. The sample used in this study is the LQ-45 company listed on the Stock Exchange, in the period from June 2015 to September 2015 totaling 45 companies. The data used are secondary data from BEI. The analysis technique used is multiple linear regression analysis.Based on the results of the exchange rate and interest rate positive effect on stock returns while market risk and trading volume have no significant effect on stock returns. Based Adjusted R Square is seen that the magnitude of the coefficient of determination of 0.212, so the only independent variable can explain stock returns of 21.2%.